Requirements to Be a Teacher in Brazil : Effective or Not? - Ponte Barbosa, Marcelo; Oliveira Costa, Leandro (World Bank, Washington, DC, 2019)
Policy makers in Brazil attempted to improve human capital through changes in the legislated requirements for teacher education in 1996. They passed a national Law of Guidelines and Standards of Education that established 2007 as the deadline for all Brazilian basic education teachers to have tertiary education–level qualifications. This implied a significant change in the profile of teachers in basic education and in the provision of pre-service training. The objective of this study is to investigate the effects of the increase in the share of public upper secondary school teachers with higher education on students’ performance in math and Portuguese and analyze the role of the pre-service training framework in the quality of teachers in recent years. The study carried out an empirical analysis to estimate the average treatment effect on the treated on public upper secondary students through the combination of difference-in-difference and propensity score matching methods. The analysis found no evidence of positive effects on Portuguese scores, and despite the statistically significant positive effect of the rise in teachers with higher education on math scores, there was no effect from specific math training. Finally, the paper discusses the possible reason for the ineffectiveness of teacher pre-service training, such as the quality of the training delivered by distance learning modalities and the low performance of the secondary students who enter the teacher schools.